THE RECEPTION ANALYSIS OF BREAST-FEEDING MOTHERS TOWARDS INSTAGRAM FEEDS OF @OLEVELOVE ACCOUNT - Widodo, Jordy Satria; Narendra Wigati, Oki Turatula (Asosiasi Pusat Studi Wanita/Gender & Anak Indonesia (ASWGI), 2021)
Breastfeeding for working moms have been importantly done inasmuch as it results in the fulfillment of infants’ rights in getting the optimal health. Moreover, through the Government Regulation No. 33 year 2012 on Exclusive Breastfeeding, it is noted that the activity is advised to be supported by the surroundings, such as in the family, neighborhood, workplaces, and public places. There has to be an awareness-raising in encouraging all people to support the new moms while breastfeeding their infants. This research aims at investigating the reception of working moms on the feeds made by @olevelove account. The research used the qualitative approach which took reception analysis method by Stuart Hall. Moreover, the reception analysis was conducted through the in-depth interviews towards three selected Instagram feeds. There were seven informants selected with the criteria of millennial working moms, having a baby or babies, and experiencing the postpartum issues of colostrum production, baby blues syndrome, and breast-pumping at workplaces. The result shows that there is an emancipatory aspect produced by the account since it gives informative tips for the new mothers on exclusive breastfeeding. In fact, most informants stand at the dominant-hegemonic position to agree to the selected three contents from the account.